2020
DOI: 10.1111/trf.16014
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐enhanced hepatitis E virus nanofiltration during the manufacture of human immunoglobulin

Abstract: Background: Circulation of hepatitis E virus (HEV) in areas where plasma is sourced for the manufacture of plasma-derived medicinal products (PDMPs) has prompted verification of HEV clearance. HEV exists as quasi lipid-enveloped (LE) and non-lipid-enveloped (NLE) forms, which might be of relevance for HEV clearance from manufacturing processes of antibody-containing PDMPs with solvent/detergent (S/D) treatment upstream of further clearance steps. Study Design and Methods: Presence of different HEV particles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Immunoglobulins react with viruses and enlarge their size, first described by Omar & Kempf 23 and confirmed by Kreil et al 24 Further studies with HEV confirmed this enlarging effect by antibodies. 25 The publicly available data assessed here support this enlarging effect as demonstrated by a t-test comparing the LRFs for IgG intermediates and all other products (inhibitors, coagulation factor concentrates and "others") resulting in a highly significant difference in LRFs for these two categories when filtered through Planova 35N filters (Table 5). through Planova 35N-a highly significant increased LRF for B19V was demonstrated.…”
Section: Large Virus Retentive Filtersupporting
confidence: 58%
See 1 more Smart Citation
“…Immunoglobulins react with viruses and enlarge their size, first described by Omar & Kempf 23 and confirmed by Kreil et al 24 Further studies with HEV confirmed this enlarging effect by antibodies. 25 The publicly available data assessed here support this enlarging effect as demonstrated by a t-test comparing the LRFs for IgG intermediates and all other products (inhibitors, coagulation factor concentrates and "others") resulting in a highly significant difference in LRFs for these two categories when filtered through Planova 35N filters (Table 5). through Planova 35N-a highly significant increased LRF for B19V was demonstrated.…”
Section: Large Virus Retentive Filtersupporting
confidence: 58%
“…Properties of virus particles enlarging their size, for example, quasi-enveloped HEV 25 as well as antibody/virus particle complexes [23][24][25] enhancing considerably the virus removal capacity of virus retentive filters; therefore, it has to be assessed carefully whether these properties exist under defined feed stream conditions, for example, solvent/detergent treatment prior to virus filtration step and concentration of antibodies specifically reacting with viruses.…”
Section: Filtration Of Large Viruses Throughmentioning
confidence: 99%
“…Several virus clearance studies with emerging viruses were conducted. These results showed that Planova could remove emerging viruses independent of the characters of viruses (Blümel et al 2017 ; Yue et al 2019 ; Kapsch et al 2020 ). As a result, the robust virus removability of Planova was confirmed.…”
Section: Development Of Planovamentioning
confidence: 99%
“…Subsequently, the secondary particles contact each other to form a gel membrane, which undergoes regeneration and drying to become a dry membrane. A highly interconnected pore structure is formed due to the aggregation of the nodules, i.e., the secondary particles (Kesting 1985(Kesting , 1990Kamide 1990;Kamide et al 1993;van de Witte et al 1996). A membrane formed under v p 0-\ v p c has non-circular pores.…”
Section: Phase Separation Studies For the Cuprammonium Cellulose Solutionmentioning
confidence: 99%
“…However, substantial viral reduction has been demonstrated during the manufacturing process of plasma products using immunoaffinity chromatography, nanofiltration, cold ethanol fractionation and heat treatment[ 216 ]. Anti-HEV antibodies enhanced HEV removal by nanofiltration[ 217 ]. Furthermore, ultraviolet C light provided effective inactivation of HEV in platelet concentrates[ 218 ].…”
Section: How To Reduce Transfusion-transmitted Hepatitis Ementioning
confidence: 99%